Dealing with Sudden Cardiac Death: Who Deserves Device Implantation - Dicky Armein Hanafy (ACI (Acta Cardiologia Indonesiana), 2019)
Sudden cardiac death is one of the leading causes of death in the western industrial nations. Most people are affected by coronary heart disease (coronary heart disease, CHD) or heart muscle (cardiomyopathy). These can lead to life-threatening cardiac arrhythmias. If the heartbeat is too slow due to impulse or conduction disturbances, cardiac pacemakers will be implanted. High-frequency and life-threatening arrhythmias of the ventricles (ventricular tachycardia, flutter or fibrillation) cannot be treated with a pacemaker. In such cases, an implantable cardioverter-defibrillator (ICD) is used, which additionally also provides all functions of a pacemaker. The implantation of a defibrillator is appropriate if a high risk of malignant arrhythmias has been established (primary prevention). If these life-threatening cardiac arrhythmias have occurred before and are not caused by a treatable (reversible) cause, ICD implantation will be used for secondary prevention. The device can stop these life-threatening cardiac arrhythmias by delivering a shock or rapid impulse delivery (antitachycardic pacing) to prevent sudden cardiac death. Another area of application for ICD therapy is advanced heart failure (heart failure), in which both main chambers and / or different wall sections of the left ventricle no longer work synchronously. This form of cardiac insufficiency can be treated by electrical stimulation (cardiac resynchronization therapy, CRT). Since the affected patients are also at increased risk for sudden cardiac death, combination devices are usually implanted, which combine heart failure treatment by resynchronization therapy and the prevention of sudden cardiac death by life-threatening arrhythmia of the heart chambers (CRT-D device). An ICD is implanted subcutaneously or under the pectoral muscle in the area of the left collarbone. Like pacemaker implantation, ICD implantation is a routine, low-complication procedure today.